2014
DOI: 10.2337/dc14-0096
|View full text |Cite|
|
Sign up to set email alerts
|

Mortality Trends Among People With Type 1 and Type 2 Diabetes in Australia: 1997–2010

Abstract: OBJECTIVEWith improvements in cardiovascular disease (CVD) rates among people with diabetes, mortality rates may also be changing. However, these trends may be influenced by coding practices of CVD-related deaths on death certificates. We analyzed trends of mortality over 13 years in people with diabetes and quantified the potential misclassification of CVD mortality according to current coding methods. RESEARCH DESIGN AND METHODSA total of 1,136,617 Australians with diabetes registered on the National Diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
136
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(158 citation statements)
references
References 29 publications
15
136
2
5
Order By: Relevance
“…Population-based registers have shown excess mortality for individuals with Type 1 diabetes compared with the general population [1][2][3][4][5][6][7][8][9][10]. Reduced mortality in recent years for children diagnosed with Type 1 diabetes suggests decreasing excess mortality [1,2,9,11], but few studies have examined this trend in Type 1 diabetes onset among adolescents and young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Population-based registers have shown excess mortality for individuals with Type 1 diabetes compared with the general population [1][2][3][4][5][6][7][8][9][10]. Reduced mortality in recent years for children diagnosed with Type 1 diabetes suggests decreasing excess mortality [1,2,9,11], but few studies have examined this trend in Type 1 diabetes onset among adolescents and young adults.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that survival of people with type 1 diabetes relative to the general population has improved since the 1940s [6] and has continued to improve in recent years [15]. One Australian study comparing people with type 1 diabetes with the general population estimated that the standardised mortality ratio (SMR) decreased from 4.20 in 1997 to 3.08 in 2010 [16]. Similarly, LE has improved over time [5].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that the proportion of deaths attributed to cancer is increasing over time, in part due to improvements in treatment of CVD. Thus, people with diabetes are surviving longer and not dying from diseases such as CVD and then develop other outcomes such as cancer (28). Cancer is now a leading COD in diabetes, accounting for 27 and 33% of all deaths in people with type 1 and type 2 diabetes, respectively (28).…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…Thus, people with diabetes are surviving longer and not dying from diseases such as CVD and then develop other outcomes such as cancer (28). Cancer is now a leading COD in diabetes, accounting for 27 and 33% of all deaths in people with type 1 and type 2 diabetes, respectively (28). Only one other study that we are aware of has also shown that the proportion of deaths attributed to cancer among people with type 2 diabetes has increased from 23% in 1970 to 27% in 1990 (3).…”
Section: Comparison With the Literaturementioning
confidence: 99%